2019
DOI: 10.1088/1402-4896/ab154a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation into unsteady magnetohydrodynamics flow of micropolar hybrid nanofluid in porous medium

Abstract: This article provides an insight into the magnetohydrodynamic flow of time-dependent rotating hybrid nanofluids, using micropolar fluid theory. The medium containing the fluid is considered to be porous while the surface is being stretched exponentially. The mathematical composition of this problem is then numerically solved utilizing the bvp4c technique. An assessment of the flow behavior and properties of a conventional nanofluid along with those of a hybrid nanofluid, using velocity profiles, microrotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The Keller-box method is used in 27 to solve numerically a problem of gyrating MHD flow over a porous surface. Subhani and Nadeem 28 examined the time-dependent MHD flow of hybrid nanoliquid over the rotating porous surface, by considering fluid theory. Lokesh et al 29 highlighted numerically the chemical reaction of the 3D Casson nanofluid flow over an expanding surface.…”
Section: Introductionmentioning
confidence: 99%
“…The Keller-box method is used in 27 to solve numerically a problem of gyrating MHD flow over a porous surface. Subhani and Nadeem 28 examined the time-dependent MHD flow of hybrid nanoliquid over the rotating porous surface, by considering fluid theory. Lokesh et al 29 highlighted numerically the chemical reaction of the 3D Casson nanofluid flow over an expanding surface.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetohydrodynamic time-dependent liquid film flow of grapheme nanoparticles embedded nanofluid under various thermal transport aspects can be viewed in ref. 12 The influence of drag force on the flow over an expanding surface was discussed by Sheikholeslami et al 13 Later on, the researchers 14,15 investigated the transport phenomena of Newtonian and non-Newtonian hybrid nanoliquids under various physical effects. Kumar et al 16 discussed the effect of Brownian moment on bio convective stagnated motion of nanoliquid and presented dual solutions.…”
Section: Effect Of Asymmetrical Heat Rise/fall On the Film Flow Of Mamentioning
confidence: 99%
“…They found that Cu-Al 2 O 3 /water has greater heat transfer rate than nanofluid and regular fluid for some of the investigated parameters. In addition, a considerable amount of previous works on hybrid nanofluid over a porous medium have been successfully reported (e.g., [31][32][33][34][35]).…”
Section: Introductionmentioning
confidence: 99%